The Cocoa Black Ant-Mealybugrelationship: Artificial Establishment of Cataenococcus Hispidus (Homoptera: Pseudococcidae) on Cocoa - Ang, Ban Na (1988)
The cocoa black ant Dolichoderus thoracicus (Smith), plays an important role in the control of the cocoa mirid Helopeltis theobromae (Miller) in Malaysia. The ant has a mutualistic relationship with a variety of homopterans, the commonest one being the mealybug Cataenococcus hispidus (Morrison). Attempts to manipulate D. thoracicus are dependent on the ability to manipulate C. hispidus. The study carried out was aimed at obtaining information on C. hispidus to enable the mealybug to be established more successfully. A method of es timating the number of individuals in a first in star colony was devised.